Application of wheat flour (Triticum aestivum) on spore density and sporulation efficiency of Bacillus megaterium isolated from Litopenaeus vannamei gastrointestinal tract - I MADE DEDI MAHARIAWAN; WAHYU ENDRA KUSUMA; ATING YUNIARTI; M.A.G. BELTRAN; ANIK MARTINAH HARIATI (Society for Indonesian Biodiversity, 2021)
Abstract. Mahariawan IMD, Kusuma WE, Yuniarti A, Beltran MAG, Hariati AM. 2021. Application of wheat flour (Triticum aestivum) on spore density and sporulation efficiency of Bacillus megaterium isolated from Litopenaeus vannamei gastrointestinal tract. Biodiversitas 22: 3709-3715. Bacillus megaterium is frequently used in fish farming, such as white shrimp (Litopenaeus vannamei) pond, which can produce spores with high stability in its implementation. Currently, spore production still requires the availability of high-cost carbon sources. The objective of this research was to evaluate the effect of different wheat flour doses on spore density and sporulation efficiency of B. megaterium BM1. In flasks, 50 mL of each test medium was treated with different doses of wheat (10, 20, 30 and 40 g. L-1, respectively) and glucose was used as a control. Each treatment was inoculated with B. megaterium BM1 (2.6 x 108 CFU. mL-1) and incubated in a shaker incubator (120 rpm) at 37 °C for 120 hours. The results showed that the highest vegetative cell concentration (17 x 108 CFU. mL-1), growth rate (0.8 hour-1) and spore (14.7 x 108 spores. mL-1) were found in the wheat flour dose of 30 g. L-1. Furthermore, the highest sporulation efficiency was achieved at 20 g. L-1 of wheat (91.30%) and germination should be done at a dose less than 40 g. L-1. The size of the spores was 1.35-1.39 µm. Thus, 30 g. L-1 of wheat flour is a potential dose to produce spore for probiotic candidates.